The Effect of Accounting Information Systems and Information Technology on Accounting Staff Performance of Manufacturing Companies in Semarang - Yeni Kuntari; Anis Chariri; Nurdhiana Nurdhiana; Cornelio Purwantini (Jurnal Akuntansi Bisnis, 2022)
Abstract In the industrial era and in the context of the COVID-19 pandemic, today's business community requires accounting professionals with information technology skills and a good understanding of computer applications. This study investigates the effect of application utilization. and trust in the accounting information system on accounting staff performance. The sample is 210 medium and large-scale manufacturing companies in Semarang City in 2020. The survey was conducted to collect the data from the selected sample. In order to satisfy the objectives of the study, a multiple regression analysis was held. The results of this study indicate that the trust in information technology accounting systems and information technology has a positive effect on the performance of accounting staff. Meanwhile, the application of the accounting information system, the use of the accounting information system, and the effectiveness of the accounting information system have no effect on the performance of the accounting staff.AbstrakDi era industri dan dalam konteks pandemic covid 19, lingkungan bisnis menuntut kompetensi para profesional akuntansi di bidang teknologi informasi dan memahami aplikasinya dengan piranti komputer. Tujuan penelitian ini adalah mengetahui pengaruh penerapan sistem informasi akuntansi, penggunaan sistem informasi akuntansi, efektivitas sistem informasi akuntansi, kepercayaan pada sistem informasi akuntansi dan teknologi informasi terhadap kinerja pegawai bagian akuntansi. Sampel penelitian diambil dari 210 manajer akuntansi perusahaan manufaktur skala menengah dan besar di Kota Semarang. Pemerolehan data menggunakan kuesioner dan selanjutnya dianalisis dengan regresi linier berganda. Hasil penelitian menunjukkan bahwa kepercayaan pada teknologi sistem informasi akuntansi dan teknologi informasi berpengaruh positif terhadap kinerja pegawai bagian akuntansi. Penerapan sistem informasi akuntansi, penggunaan sistem informasi akuntansi, dan efektivitas sistem informasi akuntansi tidak berpengaruh terhadap kinerja pegawai bagian akuntansi.